INTEGRATED RESEARCH TOWARD SUSTAINABLE LOCAL DEVELOPMENT - Baimai, Visut (Life Sciences and Environment Journal, 2018)
Integrated research in connection with teaching students following the King’s Philosophy and Sustainable Development (understand - reach out – develop) will lead to sustainable local development in accordance with the United Nations Programme on Sustainable Development Goals (SDGs). The roots of Thai culture are agricultural society; most people are living on the surroundings of natural resources (soil – water – forest and biodiversity). Thus, integrated research for sustainable local development in terms of area - based or issue – based problems should focus on natural resources, culture and local wisdom following the concept of ecotechnology. This will keep the balance between human and nature because the balance of nature is sustainability. This approach will strengthen and sustain our social and community economic development making it balancing with capital economy currently under “Thailand 4.0” economic model that is driven by innovation, sciences and disruptive technology.